Managers’ attitudes to creativity and innovation practices in the creative industries - Sousa, Fernando Cardoso (2019)
This article seeks to demonstrate that the relationship between entrepreneurs’ attitudes towards creativity and business innovation practices is stronger in the creative industries. A sample of 454 managers of micro and medium-sized companies – of which 94 belong to the creative industries – was surveyed by making an inventory of innovative business practices and applying a scale measuring attitudes towards creativity. The results were derived based on a linear regression model with two factors for the attitudes scale (i.e. leadership and autonomy) and for the inventory of business practices (i.e. performance and strategy). This research supported the initial theoretical proposition by confirming the influence of managers’ creative attitudes towards their company’s innovative, strategy-based practices, especially within the creative industries. Innovative managers appear to be disciplined individuals driven to collaborate with their employees. Although these findings require further study, they suggest that managers in the creative industries have noteworthy characteristics.